Analysis of the Kulon Progo Bela-Beli Program on the Economy - Uswatun Khasanah; Diasa Karimahakim; Anas Usman Bello (Journal of Asset Management and Public Economy (JAMPE), 2022)
Regional or local economic development is a process of involvement of local governments and elements of society in jointly managing local resources or potentials with the aim of creating new jobs that can stimulate economic and community growth as well as alleviating people in poverty. One of the efforts to overcome these problems is the "Bela-Beli Kulon Progo" program. This study has a purpose, namely to determine the implementation of the "Bela-Beli Kulon Progo" program for the people in the Kulon Progo area. This study uses a qualitative descriptive method by using survey research. The use of this method is in accordance with the purpose of this study, which is to describe the implementation of the "Bela-Beli Kulon Progo" program for the community in the Kulon Progo area. The results of the study use two perspectives, namely the perspective of the community who are members of the "Bela-Beli Kulon Progo" Program and the perspective of stakeholders in the "Bela-Beli Kulon Progo" Program with the results obtained on the economy and community participation in the "Bela-Beli Kulon Progo" Program. directly and indirectly felt by the people of Kulon Progo Regency through employment, increasing income, increasing quality and productivity, as well as high enthusiasm and participation in the program. Other results through the role of local governments through related agencies obtained very good and efficient results through the provision of counseling, assistance, supervision, and always innovating in the "Bela-Beli Kulon Progo" Program which was felt directly and indirectly by the people of Kulon Progo Regency.